Development of E-Comic-Based Teaching Module to Enhance Students’ Mathematical Argumentation Skills - Azizah, Laili Nur; Tristanti, Lia Budi; Iffah, Jauhara Dian Nurul (FKIP Universitas Lampung, 2025)
This study aims to develop an e-comic-based teaching module to enhance students’ mathematical argumentation skills on the topic of Systems of Linear Equations in Two Variables (SPLDV), referring to the Toulmin Argumentation Framework (data, claim, warrant, backing, rebuttal, and qualifier). The study employed a Research and Development (R&D) design using the ADDIE development model. It was conducted at one of the public junior high schools in Jombang, East Java, Indonesia, involving 25 students and two teachers as respondents. The research instruments included expert validation sheets, questionnaires for teachers and students, and a mathematical argumentation skills test developed based on the elements of the Toulmin framework. The effectiveness was evaluated using a one-group pretest–posttest approach, in which all participants were given mathematical argumentation tests before and after learning with the e-comic module. Data were analyzed using a paired sample t-test with SPSS to determine significant differences between the pre-test and post-test results. The expert validation results showed that the e-comic-based module obtained an average score of 94.23%, categorized as very valid, indicating strong content alignment, instructional design quality, and classroom applicability. The practicality test revealed that teacher responses averaged 94% and student responses 82%, both categorized as very practical, demonstrating that the module is easy to use, engaging, and relevant to students’ learning needs. The effectiveness test yielded a significance value of 0.000 (< 0.05), which reflects the module’s potential to enhance students’ mathematical argumentation skills. Pedagogically, the integration of the Toulmin framework in the e-comic context effectively helps students construct logical, structured, and evidence-based mathematical arguments through contextual narrative visualization. This approach also enhances students’ motivation, engagement, and reflective thinking during the learning process. Therefore, the developed e-comic-based teaching module is valid, practical, and effective in improving students’ mathematical argumentation skills and in supporting active, reflective, and meaningful mathematics learning. Keywords: teaching module, digital technology, e-comic, mathematical argumentation skills.